Factors influencing the speed of correction speed of distal tibial valgus deformity in children with percutaneous epiphyseodesis using transphyseal screw - Dussa, Chakravarthy Ugandhar; Böhm, Harald; Meister, Florian (Foot and Ankle Surgery, 2024)
Introduction: The distal tibial valgus deformity in children mimics a hindfoot valgus and is observed in several conditions of both non-neurogenic and neurogenic origin. The deformity can only be detected with radiological examination and can be safely and effectively corrected in children with medial percutaneous epiphysiodesis using transphyseal screws (PETS). The aims of the study are: 1. to determine the correction rates of the distal tibial valgus deformity due to different pathologies, 2. to examine the correction rate in relation to the age at implantation, severity of the initial deformity and the duration of implantation, 3. and types of foot deformities associated with the deformity. Materials and methods: A retrospective study was done on children who underwent a PETS for a distal tibial valgus deformity. The lateral distal tibia angle 89° ± 3° on ankle mortice x-rays was taken as normal. An analysis of variance and covariance was done to investigate differences in parameters between aetiologies and relations between parameters respectively. Results: Following exclusion of 191 limbs, 155 limbs in 104 children were included the study, 5 groups could be identified: Idiopathic, ICP (cerebral palsy), MMC (Meningomyelocele), Dysmelia, MHE (multiple hereditary exostosis). The mean age at implantation of all patients was 10.9 ± 1.4 years. The average correction of 0.45° ± 0.08°/month with no significant differences in the correction rates between groups. However, the correction rates were dependent on the age, the initial deformity and the duration of treatment. The incidence of a valgus foot deformity was 86.4 %. Conclusion: The correction rates of the distal tibial valgus deformity following PETS are variable and depend, on the age at implantation, duration of treatment and initial deformity. The spectrum of foot deformities associated with distal tibial valgus deformity, especially a high prevalence of valgus foot deformity warrants an ankle mortice x-ray. Level of Evidence: Level III, retrospective study
CRIS-Team Scopus Importer:2024-11-15
Keywords: Age; Ankle valgus; Correction rate; Growth-plate. LDTA; Hemiepiphysiodesis; PETS; Screw; Valgus deformity of the distal tibia